Recent (Re)Visions of Canlit: Partial Stock-Taking - Rzepa, Agnieszka (Studia Anglica Posnaniensia, 2020)
This article approaches recent discussions on the state of contemporary CanLit as a body of literary texts, an academic field, and an institution. The discussion is informed primarily by a number of recent or relatively recent publications, such as Trans.CanLit. Resituating the Study of Canadian Literature (Kamboureli & Miki 2007), Refuse. CanLit in Ruins (McGregor, Rak & Wunker 2018), Luminous Ink: Writers on Writing in Canada (McWatt, Maharaj & Brand 2018), and the discussions and/or controversies some of those generated – expressed through newspaper and magazine articles, scholarly essays, but also through tweets, etc. The texts have been written as a response to the current state and – in some cases – scandals of CanLit. Many constitute attempts at starting or contributing to a discussion aimed at not only taking stock of, but also reinterpreting and re-defining the field and the institution in view of the challenges of the globalising world. Perhaps more importantly, they address also the challenges resulting from the rift between CanLit as implicated in the (post)colonial nation-building project and rigid institutional structures, perpetuating the silencings, erasures, and hierarchies resulting from such entanglements, and actual literary texts produced by an increasingly diversified group of writers working with a widening range of topics and genres, and creating often intimate, autobiographically inspired art with a sense of responsibility to marginalised communities. The article concludes with the example of Indigenous writing and the position some young Indigenous writers take in the current discussions.